A Virus-derived stacked RNAi construct confers robust resistance to cassava brown streak disease - Beyene, Getu; Chauhan, Raj Deepika; Ilyas, Muhammad; Wagaba, Henry; Fauquet, Claude M.; Miano, Douglas; Alicai, Titus; Taylor, Nigel J. (Frontiers Media, 2017)
Cassava brown streak disease (CBSD) threatens food and economic security for smallholder farmers throughout East and Central Africa, and poses a threat to cassava production in West Africa. CBSD is caused by two whitefly-transmitted virus species: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) (Genus: Ipomovirus, Family Potyviridae). Although varying levels of tolerance have been achieved through conventional breeding, to date, effective resistance to CBSD within East African cassava germplasm has not been identified. RNAi technology was utilized to integrate CBSD resistance into the Ugandan farmer-preferred cassava cultivar TME 204. Transgenic plant lines were generated expressing an inverted repeat construct (p5001) derived from coat-protein (CP) sequences of CBSV and UCBSV fused in tandem. Northern blots using probes specific for each CP sequence were performed to characterize 169 independent transgenic lines for accumulation of CP-derived siRNAs. Transgenic plant lines accumulating low, medium and high levels of siRNAs were bud graft challenged with the virulent CBSV Naliendele isolate alone or in combination with UCBSV. Resistance to CBSD in the greenhouse directly correlated to levels of CP-derived siRNAs as determined by visual assessment of leaf and storage root symptoms, and RT-PCR diagnosis for presence of the pathogens. Low expressing lines were found to be susceptible to CBSV and UCBSV, while medium to high accumulating plant lines were resistant to both virus species. Absence of detectable virus in the best performing p5001 transgenic lines was further confirmed by back-inoculation via sap or graft challenge to CBSD susceptible Nicotiana benthamiana and cassava cultivar 60444, respectively. Data presented shows robust resistance of transgenic p5001 TME 204 lines to both CBSV and UCBSV under greenhouse conditions. Levels of resistance correlated directly with levels of transgene derived siRNA expression such that the latter can be used as predictor of resistance to CBSD.